Netiquette of using internet - Rasulov, Xushnud (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Nowadays, in the world of information, the era of the Internet, the rapid development of multi-media information technology such as Internet TV, Internet radio, email, online video, and their audience and influence are expanding.There is no need to talk too much. Such informationthe tools of the young people with a great deal of interest, and from themIsak, which is widely used, is really itit is difficult to understand the importance of the matter